KEMULIAAN DAN PERGESERAN MAKNA GURU - Yasa, Putu Dana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
A teacher has a very important role and responsibility for change and improving the quality of students. The responsibility of a teacher must be believed and realized so that the teacher really gives true knowledge in the teaching process. The Hindu view in understanding the meaning of the word